Consumer Buying Behaviour Model for Toothpastes - Vani, G.; Ganesh Babu, M.; Panchanatham, N. (Indian Journal of Marketing, 2011)
Understanding consumer behavior is an important task for the company to successfully sell the product in the market. Consumer decision-making models clearly explain the stages involved in decision-making, but it depends upon the product or service nature and the type they are undergoing in the stages. For example, the consumer spends more time for deciding a brand for purchasing shopping goods like TV, Washing machine etc. The risk involved is more in shopping and specialty goods when compared to convenience goods like FMCG products (Toothpaste, soap, food products etc.). There are many models developed by researchers for understanding consumer behavior. The marketers have to select the suitable model depending upon the product nature. This analysis clearly explains which model is suitable for purchasing toothpaste and what are the factors influencing the consumer for buying toothpastes. Generally, the awareness level of people dominates their decision for selecting a product and a brand. For buying toothpaste, personality, life style, demographic and behavioral factors are the most important influencing factors in selecting a particular brand. The firms' contribution also influences the consumer for decision making. The stages involved in decision making for buying toothpaste are also clearly explained in this article. This study is useful for companies and researchers to get insight into the buying behavior of toothpaste.